2021
DOI: 10.3390/agriculture11070626
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Sulphur—The Once Neglected Nutrient: It’s Roles in Plant Growth, Metabolism, Stress Tolerance and Crop Production

Abstract: Sulphur plays crucial roles in plant growth and development, with its functions ranging from being a structural constituent of macro-biomolecules to modulating several physiological processes and tolerance to abiotic stresses. In spite of these numerous sulphur roles being well acknowledged, agriculture has paid scant regard for sulphur nutrition, until only recently. Serious problems related to soil sulphur deficiencies have emerged and the intensification of food, fiber, and animal production is escalating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
61
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 100 publications
(204 reference statements)
3
61
0
2
Order By: Relevance
“…It has been observed that, without presence of adequate sulfur (S) in soil, plants/crops cannot complete their life cycle adequately in terms of yield, quality or protein content in seeds, nor can they make optimum utilization of supplied N, required for protein and enzyme synthesis [ 7 ]. Sulfur compounds like tripeptide glutathione (GSH) are involved in detoxification of reactive oxygen species (ROS) in response to various abiotic and biotic stresses; it also acts as a substrate for the biosynthesis of phytochelatins and/or glucosinolates (GSLs) in response to defense against herbivores and other pathogens [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that, without presence of adequate sulfur (S) in soil, plants/crops cannot complete their life cycle adequately in terms of yield, quality or protein content in seeds, nor can they make optimum utilization of supplied N, required for protein and enzyme synthesis [ 7 ]. Sulfur compounds like tripeptide glutathione (GSH) are involved in detoxification of reactive oxygen species (ROS) in response to various abiotic and biotic stresses; it also acts as a substrate for the biosynthesis of phytochelatins and/or glucosinolates (GSLs) in response to defense against herbivores and other pathogens [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur is an essential macronutrient for plants and a constituent of relevant biomolecules, such as the amino acids methionine and cysteine, the antioxidant glutathione, glucosinolates, coenzymes and prosthetic groups [1]. As such, the availability of S, the main source of sulfur in soils, is an important determinant of plant growth, yield and quality.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur plays an important role in the protection against environmental stresses, too. As Sulfur is not mobile in the plant, a continuous supply of Sulfur is needed for optimum crop performance [24].…”
Section: Introductionmentioning
confidence: 99%